PRAKTIK MANAJEMEN PEMERINTAHAN DALAM PENGENDALIAN PEMANFAATAN RUANG ZONA LINDUNG DI DESA ECATU KABUPATEN BADUNG - Utama, Rhesa Anggara; Priantara, I Komang Triska Ananda Dilivianugraha (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
This study examines spatial utilization within the dynamics of regional governance, focusing on the effectiveness of spatial control in the protected zone of Pecatu Village, Bali. Guided by the framework of local government management functions, the research analyzes how the four key governmental management functions planning, organizing, actuating, and controlling operate in regulating land use within this protected area. Employing a qualitative approach, data were collected through in-depth interviews, participatory observation, and document analysis, with informants selected purposively based on predefined criteria. The findings indicate that the Badung Regency Government has implemented the planning and organizing functions adequately, evidenced by the integration of spatial control into regional planning documents and the clear distribution of institutional roles. However, the actuating function, particularly the operationalization of monitoring and enforcement, remains suboptimal. Monitoring tends to be reactive, while enforcement is sporadic and lacks continuity, as illustrated by long-standing violations such as cliff-edge development at Bingin Beach, which was only addressed in 2025. The study concludes that although governmental management practices are in place, their effectiveness is significantly constrained by institutional limitations, resource shortages, and pressures from the tourism sector. Strengthening actuating and control functions, enhancing human resource capacity, improving cross-sectoral coordination, and engaging local communities in monitoring systems are recommended to ensure sustainable protection of the area.